Analisis Perbandingan Output Daya Listrik Panel Surya Sistem Tracking Dengan Solar Reflector: Analisis Perbandingan Output Daya Listrik Panel Surya Sistem Tracking Dengan Solar Reflector - Dwi Cahyanto, Wahyu; Winarno, Istiyo; Dewantara, Belly Yan (J-Eltrik, 2024)
At this time, one type of alternative energy that is growing rapidly and is widely used by many countries is solar energy which is used as a power plant in the form of solar cells. This technology can convert the intensity of the sun into electrical energy. In its development, a control system is needed to optimize the output power of solar cells, such systems are using solar tracking which can control the position of solar cells so that they are always perpendicular to the direction of the sun automatically and a solar reflector that uses a flat mirror as optics to optimize light intensity. The system used for this arrangement is called a solar tracking and reflector system with Adaptive Neuro Fuzzy Inference System (ANFIS) control. The results obtained from the tracking system after testing the most optimal power obtained when the solar cell is perpendicular to the sun with ANFIS control which is 12,743 watts and the solar cell with reflector can optimize power twice as much..